Promising role of topical caffeine mesoporous gel in collagen resynthesis and UV protection through proline assessment - Mae Seleem; Y. S. Abulfadl; NadaEl Hoffy; Nancy M. Lotfy; Heba A. Ewida (SpringerOpen, 2022)
Abstract Background Caffeine, an alkaloid agent, has been globally used regularly in drinks, for the reduction in skin cancers and wrinkle formation. As a result of the previous, attempts have been carried out to use caffeine in cosmetology due to its antioxidant and UV ray protection effects. Our aim was to evaluate the effect of caffeine on collagen resynthesis via its effect on proline and prolidase biosynthesis on mice, orally and topically as mesoporous silica at three levels, and the influence on UV protection. In skin biopsies of orally and topically treated mice, the following was assessed using ELISA and Western blot techniques, the activity of prolidase, together with the concentrations of proline, beta integrin, insulin growth factor, protein kinases beta, and mitogen-activated protein kinase. Moreover, we loaded the caffeine on mesoporous silica and assessed the aforementioned parameters together with checkpoint kinase 1 and Rad3-related protein. Results Caffeine promoted collagen resynthesis in a dose-dependent manner. The mechanism of this process was found at the level of prolidase activity as caffeine significantly increased the enzyme activity. Caffeine also had a protective effect against UV exhibited by the over-expression of beta integrin, insulin growth factor together with the under-expression of protein kinases beta, mitogen-activated protein kinase, checkpoint kinase 1, and Rad3-related protein. Conclusions Our study revealed the superiority of SYL-C12 (mesoporous silica-loaded caffeine gel), compromising the high level of the three independent factors, in terms of the measured responses in mesoporous silica with caffeine. Moreover, caffeine promoted collagen resynthesis with significant protective effect against UV apoptotic damage.